Characterization of human body channel for oblique incident case of plane wave in the 0.1-10 GHz frequency band for special health care monitoring application - Zeinelabedeen, Wael; Uyguroglu, Rasime (IEEE, 2020)
Antenna and communication technology play the key role in the applications of body healthcare monitoring systems. In these applications, the system should transmit data over a certain distance which include part of the human body. This paper demonstrates the variation of characteristic behavior of the human body channel according to the incident angle of electromagnetic (EM) wave on multilayered planar human tissue in the range of frequencies from 100 MHz to 10 GHz. The study includes simulations by the microwave simulation software CST for monitoring the oblique and transverse fractured bone as a new healthcare monitoring application depending on the oblique incident of EM wave.
28th Signal Processing and Communications Applications Conference (SIU) -- OCT 05-07, 2020 -- ELECTR NETWORK
Keywords: implanted antenna; oblique incident; multilayered tissue